IMPLEMENTASI APLIKASI SISTEM INFORMASI PEMERINTAHAN DAERAH (SIPD) PADA DINAS TRANSMIGRASI DAN TENAGA KERJA KABUPATEN ACEH BARAT - Nadya Balqis; Zuhrizal Fadhly; Maulyanda Az (Jurnal Ilmiah Wahana Bhakti Praja, 2021)
To create accurate information, the Ministry of Home Affairs designed an application for the Regional Government Information System (SIPD) as a useful application to achieve a successful coordination between the central government and regional governments. The implementation of SIPD is also aimed at the realization of good government, implementation of data technology-based regional planning and budgeting management. The implementation of SIPD is also to carry out the policies of each program of the West Aceh Regency Government activities, especially the Transmigration and Manpower Office. The case in this research is the implementation of SIPD at the Department of Transmigration and Manpower Kab. West Aceh. The object under study is the implementation of the SIPD application. The analytical model used in this research is descriptive qualitative analysis, using Edward III's theory of Communication, Human Resources, Disposition and Bureaucratic Structure. This theory is used to see where there are obstacles in the implementation of the Regional Government Information System (SIPD) application. The results of the analysis of the implementation of the Regional Government Information System (SIPD) application at the Transmigration and Manpower Office of the Regency. Aceh Barat from the four indicators of Edward III's theory covering the dimensions of Communication, Human Resources, Disposition and Bureaucratic Structure, there are still obstacles in the communication dimension; resource; and disposition. significantly, and there are obstacles in other dimensions, namely the time in using the SIPD application. Thus, Special Education and Training is needed to provide more understanding for SIPD application users, especially users in related agencies. Keywords: implementation, application, SIPD, Transmigration and Manpower Office, West Aceh